The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpubh.2021.662166
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Finance, Environmental Regulation, and Public Health in China: Lessons for the COVID-19 Pandemic

Abstract: The slow-down of the Chinese economy and the depression in the global economy during the COVID-19 show that governments should provide stimulus packages. These policies should be inclusive in terms of financial gains. Using the panel data of 30 regions in China from 2006 to 2016, this paper uses the Poisson Pseudo-Maximum Likelihood (PPML) estimator to analyze the impact of inclusive finance on public health. The results show that inclusive finance has a significant positive effect on public health. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…During the pandemic, economies of the political powers were affected, in particular due to the restriction of economic trade, so that the governments of these countries had to act in terms of health protection but also to stimulate the affected domestic business environment in the global trade segment in order to recover. The authors [ 13 ] propose a system based on PPML (Poisson Pseudo-Maximum Likelihood) estimators, so that the financial development mechanism strengthens public health care by promoting financial flows through state-owned firms. While this may be negative in the long term, in the short term, the proposed solution may achieve its goal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the pandemic, economies of the political powers were affected, in particular due to the restriction of economic trade, so that the governments of these countries had to act in terms of health protection but also to stimulate the affected domestic business environment in the global trade segment in order to recover. The authors [ 13 ] propose a system based on PPML (Poisson Pseudo-Maximum Likelihood) estimators, so that the financial development mechanism strengthens public health care by promoting financial flows through state-owned firms. While this may be negative in the long term, in the short term, the proposed solution may achieve its goal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also assert that due to rapid economic growth and a high amount of fossil fuel consumption, the health of the population is severely affected due to carbon emission. Similarly, Chen et al ( 32 ), Liu and Guo ( 33 ) and Zhao et al ( 34 ) also addressed the relationship between carbon emission and public health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research in China has drawn a relatively consistent conclusion: green credit has a positive impact on health. Liu and Guo (12) discussed the significant positive effect of inclusive finance on public health based on China's data. Hu et al (13) found that China's green credit has significant effects on the transformation of the industrial structure.…”
Section: Green Credit and Healthmentioning
confidence: 99%
“…λ i represents the fixed effect, and µ it and v it represent the residuals, assuming that they all follow a normal distribution and are independent of one another. Substituting Equation (13) into Equation (12), we obtain:…”
Section: Mediation E Ect Modelmentioning
confidence: 99%
See 1 more Smart Citation